ANALISIS KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH DALAM PRAKTIK PENGELOLAAN SEKOLAH DASAR - Hidayati, Nurul; Ahmad Thohirin; Suyitno (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research aims to describe and analyze the principal's transformational leadership strategies in managing elementary schools at UPT Satuan Pendidikan SDN Tampung II and SDN Sumber Glagah, Rembang District. The main focus of this study is how principals who are graduates of the "Guru Penggerak" (Mover Teacher) Program implement transformational values within different school environmental contexts. This research employs a qualitative approach with a multi-site study design. Data were collected through in-depth interviews, participant observation, and documentation. Data analysis techniques include data condensation, data display, and conclusion drawing/verification, conducted both within individual sites and across sites. The research results are expected to reveal the principal's strategies in motivating teachers, creating instructional innovations, and identifying supporting and inhibiting factors in the application of transformational leadership at the elementary school level. These findings contribute to the development of educational management models based on instructional leadership that is adaptive to the dynamics of modern education